Socio-macroeconomic impacts of implementing different post-Brexit UK energy reduction targets to 2030. (November 2021) - Nieto, Jaime; Pollitt, Hector; Brockway, Paul E.; Clements, Lucy; Sakai, Marco; Barrett, John
Abstract: For the period since 2011, the UK has been bound by European Union (EU) legislation regarding energy reduction targets to 2020. As of 2019, the UK had reduced its final energy use by 18% against a baseline projection to 2020, on track to meet its target of 18%. Whilst the rest of the EU-27 now set their own energy reduction targets to 2030, upon leaving the EU via Brexit, the UK is now free to choose its own energy targets. But what should the energy target be for 2030, and what are the socio-macroeconomic impacts and policy implications? To address this, we use two econometric energy-economy models to assess three different levels of energy reduction target, with 27%, 33% and 40% reduction in 2030 versus the baseline model projections. We find the strictest (40%) energy reduction target could deliver the largest economic and employment benefits. However, careful attention to policies are required, to ensure improvements to overall economy-wide energy efficiency whilst minimising rebound. Demand-side policies of serious scale within an 'avoid-shift-improve' framework are required, including massive building retrofits, significant improvements to industrial energy efficiency, switching to low energy transport modes, and moving away from meat-based diets. Highlights: We study UK energy target options and socio-macroeconomic and policy implications. The strictest energy reduction target yields the largest GDP and employment gains. If thermodynamic limits are considered, energy reduction targets lead to GDP decline. Careful attention to policies can improve energy efficiency and minimise rebound. Significant demand-side policies in an avoid-shift-improve framework are required.